2013
DOI: 10.4103/2249-4847.109245
|View full text |Cite
|
Sign up to set email alerts
|

An interesting observation of PDA closure with oral paracetamol in preterm neonates

Abstract: Patent ductus arteriosus (PDA), in which there is a persistent communication between the descending thoracic aorta and the pulmonary artery that results from failure of normal physiologic closure of the fetal ductus, is one of the more common congenital heart defects in preterm neonates. The closure of PDA can be done with either Indomethacin or Brufen which are cyclooxygenase 1, 2 inhibitor; however these drugs are associated with side effects. We report an interesting findings of ductal closure in 10 preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 8 publications
0
34
1
6
Order By: Relevance
“…This result should be interpreted with caution considering the high proportion of subjects with GA >28 weeks treated with low doses 11 20…”
Section: Discussionmentioning
confidence: 87%
“…This result should be interpreted with caution considering the high proportion of subjects with GA >28 weeks treated with low doses 11 20…”
Section: Discussionmentioning
confidence: 87%
“…The case reports explored the use of enteral and IV-administered acetaminophen when traditional ibuprofen or indomethacin therapy had failed or was contraindicated. [15][16][17][18][19][20][21][22][23][24][25][26] The 2 controlled trials compared off-label use of oral acetaminophen and oral ibuprofen for PDA treatment. Previous trials have demonstrated that oral ibuprofen has efficacy equivalent to that of the IV formulation when an identical dosing regimen is used.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] For case series using intravenous paracetamol, the proportion of successful PDA closure was between 75 and 100%.12-15 Our design was similar, but we had a larger sample size compared to previous case series. The proportion of successful PDA closure was lower at 65.5%, than in the four previous case series.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol acts as a peroxidase inhibitor in prostaglandin synthesis. 4 In previous case series involving a limited number of subjects, both oral [5][6][7][8][9][10][11][12] and intravenous preparation [12][13][14][15] of paracetamol showed satisfactory results for PDA closure, with no liver toxicity. Moreover, two randomized, double-blind, control trials showed that oral paracetamol was better than oral ibuprofen.…”
mentioning
confidence: 99%